Fruit and Vegetable Consumption, Fat Intake, and Physical Activity Participation in Relation to Socio-demographic Factors Among Medically Underserved Adults - Amir A. Hadi Alakaam; Jennifer L. Lemacks (AIMS Press, 2015)
Fruit and vegetable intake as well as physical activity participation in Mississippi is consistently lower than recommendations. We conducted a cross-sectional study to examine fruit and vegetables consumption, fat intake, and moderate-intensity physical activity participation and how these variables relate to socio-demographic factors among medically underserved adults in south Mississippi. Fruit and vegetable consumption and fat intake along with physical activity participation and socio-demographic characteristics was collected from a sample of 161 (48 male and 113 female) adults in south Mississippi. A majority (81.9%) of participants reported consuming less than five servings of fruits and vegetables per day and 54% reported exercising less than three times a week. Only 14% of participants reported eating a low fat diet. Bivariate correlations revealed no significant relationships between fruit and vegetable consumption and fat intake as well as no significant relationships between fruit and vegetable consumption and gender, ethnicity, income, marital status, or education. However, there were significant correlations between physical activity and fat intake (r = -0.21, p = 0.01), and physical activity with fruit and vegetable consumption (r = 0.16, p = 0.05). Higher physical activity rates were associated with decreased fat intake and increased fruit and vegetable consumption. Physical activity was also higher among men (r = -0.16, p = 0.05) and positively correlated with income level (r = 0.21 p = 0.01). In order to effectively identify or develop strategies to improve health by promoting increased fruit and vegetable intake and physical activity, further research is needed to understand the factors that affect behavior choices regarding nutrition and physical activity in this medically underserved adult population.